What Drives and Hinders the Use of New e-Customs Systems in Developing Countries of Sub-Saharan Africa? An Empirical Study from Cameroon - Chung, Hyorim; Cha, Kyungjin; Lee, Heejin (Information & Media, 2023)
While the adoption and replacement projects of e-government systems are increasing in developing countries, empirical research is rare. Moreover, studies on factors affecting user satisfaction of e-customs systems are limited. To fill the gap, this paper empirically investigates the e-customs system implemented by Korea and currently in operation in Cameroon, examining its facilitators and hindrances. This study marks a new approach to studying e-government systems as an ICT4D project in a developing country by creating and validating a newly developed model based on the UTAUT and the SQBT. An empirical study using a survey was conducted. Data were collected from internal and external users who had experienced both the old system (ASYCUDA++) and the new one (CAMCIS). Performance expectancy and uncertainty costs strongly affect the switching benefits and costs. Sunk costs have no significant impacts. The switching benefits and costs significantly influence the behavioral intention and user satisfaction regarding the system. The study adds value to the research fields of user resistance and IT/IS acceptance by conducting empirical research on e-customs systems implemented by a donor in a recipient country. The study gives insights to those policymakers, system developers and managers involved in ICT4D projects about the factors that are important to maximize the benefits and avoid the losses in using a new system.
Keywords: developing countries; e-customs system; user satisfaction; user resistance; adoption